Voice over IP service and performance in satellite networks. - Nguyen, T. (IEEE Communications magazine)
Voice over IP services have emerged as a low-cost alternative to PSTN voice service, and an attractive solution for voice/data integration in public and private networks. Satellite systems, as an integral part of the global communications infrastructure, already have an increasing portion of their capacities used to carry data packets, and with their global coverage and reach to remote areas are well positioned to enable growth of VoIP services. For VoIP over satellite, several issues need to be addressed. These include transmission and quality of service issues, as well as service-related issues such as service creation and customization, support of IN and supplementary services, and seamless integration with the PSTN. While the service-related aspects of VoIP are common to both terrestrial and satellite networks, transport-related issues are different. This article reports performance results of laboratory experiments for evaluating VoIP over satellite under different link and traffic conditions